Role of droplet distortion and break-up in large droplet aircraft icing - Luxford, Geoffrey; Hammond, David W.; Ivey, Paul C. (Cranfield University, 2004)
Experimental and analytical evidence is presented to illustrate droplet distortion and potential break-up in the flow conditions similar those of a drizzle droplet in the vicinity of an aerofoil. The droplet size range considered is 100u m to 500u m. The current research is at ambient temperature but with equivalent parametric conditions to SLD icing. While the results support the contention that smaller droplets, <100u m, remain essentially spherical, the larger droplets become sufficiently distorted to affect their drag characteristics and can break up due to the transient aerodynamic forces.